Dengan Sastra Menjadi Manusia - Riris K. Toha Sarumpaet (HISKI, 2007)
This paper looks into the nooks and crannies of the teaching of literature in relation to the implementation of the Kurikulum Berbasis Kompetensi (KBK) and Kurikulum Tingkat Satuan Pendidikan (KTSP). There are three elements that should be used as a guideline in implementing the KBK and KTSP: students as human beings with a capacity to grow up, literary works, and the teaching of literature.